2022
DOI: 10.1186/s12887-022-03373-4
|View full text |Cite
|
Sign up to set email alerts
|

Factors of body dissatisfaction among lebanese adolescents: the indirect effect of self-esteem between mental health and body dissatisfaction

Abstract: Background Body dissatisfaction (BD) rates are alarmingly high, especially among adolescents, thus. Having a better understanding of correlates associated with BD seems to be an important issue in this developmental context. Furthermore, as adolescence is an essential time in the development of self-perception and self-esteem the current study assesses factors associated with BD among Lebanese adolescents and evaluates the indirect effect of self-esteem between depression/anxiety/stress and BD.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 71 publications
0
10
0
2
Order By: Relevance
“…Higher total scores reflect higher levels of body dissatisfaction [ 60 ]. This measure has previously been used to assess body dissatisfaction in the Lebanese general population (e.g., [ 61 , 62 ]). In the present sample study, McDonald’s ω was 0.69.…”
Section: Methodsmentioning
confidence: 99%
“…Higher total scores reflect higher levels of body dissatisfaction [ 60 ]. This measure has previously been used to assess body dissatisfaction in the Lebanese general population (e.g., [ 61 , 62 ]). In the present sample study, McDonald’s ω was 0.69.…”
Section: Methodsmentioning
confidence: 99%
“…Higher scores correspond to a higher level of body dissatisfaction [ 48 ]. The Arabic version of the scale was used in a previous study [ 49 ]. The Cronbach’s alpha in this study was 0.60.…”
Section: Methodsmentioning
confidence: 99%
“…Particularly in Lebanon, studies documented high prevalence rates of ED symptoms in clinical populations (estimated as 46.1% for bulimia nervosa, 39.4% for anorexia nervosa, and 14.4% for binge eating) [17]. Lebanese studies in non-clinical populations also showed alarmingly high prevalence of ED pathology, such as orthorexia nervosa tendencies and behaviors (75.2%) [18], restrained eating (48.3%) [19] and disordered eating attitudes (23.8-25.3%) [20] in healthy adults, and body dissatisfaction in adolescents (45.1%) [21]. Another Lebanese study found that 36% of university students were slightly to extremely worried about their body image [22].…”
Section: Introductionmentioning
confidence: 99%